Jiawei Runjing Decoction Improves Spermatogenesis of Cryptozoospermia With Varicocele by Regulating the Testicular Microenvironment: Two-Center Prospective Cohort Study - Liu, Huang; Huang, Zhongwang; Zheng, Houbin; Zhu, Zhiyong; Yang, Hui; Liu, Xingzhang; Pang, Tao; He, Liping; Lin, Hai; Hu, Lei; Zeng, Qingqi; Han, Lanying (Frontiers in Pharmacology, 2022)
Objective: The aim of the study was to explore the evidence of JWRJD in the treatment of cryptozoospermia. Methods: A total of 162 cryptozoospermia patients with varicocele who refused to undergo surgery were included from January 2021 to December 2021. They were divided into the Jiawei Runjing Decoction group (group A), tamoxifen group (group B), and no treatment group (group C), and after the follow-up for 3 months, therapeutic effectiveness was compared. Network pharmacology was used to analyze and validate the effects and mechanisms of JWRJD. Results: Fifty-eight patients were treated with JWRJD, 55 with tamoxifen, and 49 without any treatment. After treatment, five patients were lost: one in group A, one in group B, and three in group C. The sperm count and the decrease of FSH in group A were significantly higher, but the degree of decline in the testicular volume and the degree of vein expansion have decreased significantly, which were closely related to the testicular volume (TV) [especially changes in the left testicular volume (ΔL-TV)], citric acid (CC) and its changes (ΔCC), and the vein width (VW) [especially left spermatic vein width (L-VW) and mean vein width (M-VW) and their changes (ΔL-VW and ΔM-VW)], as well as the sperm count before the treatment (bSC), which were the significant indexes to predict the therapeutic effect, especially for patients >35 years old and with grade III varicoceles. Network pharmacological analysis verifies that it can be regulated by fluid shear stress and the atherosclerosis pathway to improve the testicular microenvironment for spermatogenesis. Conclusion: JWRJD may promote spermatogenesis in cryptozoospermia patients with varicocele, which may be closely related to improving the testicular microenvironment, especially for >35 year olds and grade III varicocele patients.